Manufacture of Quartirolo cheese using exopolysaccharide-producing starter cultures - Moreira, Maria del Rosario (2003)
The capacity of some strains of Lactic Acid Bacteria (LAB) to produce exopolysaccharides (EPS) has been used in the dairy industry to improve the rheological characteristics of fermented milks and soft cheese (4). In a previous work we showed that sodium formate (SF) can stimulate the growth and proteolytic activity of L. bulgaricus (LBB) (2). In this work the effects of SF on EPS production are evaluated for the elaboration of soft cheese, Quartirolo type. The results showed significantly differences in moisture content, meltability, proteolytic activity and texture between cheeses made using EPS+ strains (mixed-starter cultures prepared with L. bulgaricus+S. thermophilus, LBB+CP2 and single-strain culture plus SF, LBB+ SF) and cheeses made with a control culture (LBB). On the other hand, hardness, meltability and proteolytic activity were similar between cheeses made with mixed starters cultures (LBB+CP2) and single strain plus SF (LBB+SF). As expected, cheese moisture levels and meltability were significantly higher in cheese made with mixed-starter culture (LBB+CP2) and single-strain plus SF (LBB+ SF) respect to the control, LBB. These results suggest that EPS+ starter cultures could be used to increase cheese moisture content and to improve meltability, textural and proteolytic properties, respect to the cheeses made with single strain starter (LBB).